Mental well-being and labor optimism in tourist employees of a region of Peru - Paredes-Pérez, Marco A. J. (2023)
The objective of the study was to determine the relationship between mental well-being and work optimism in tourism collaborators in the Junín region, Peru. The paradigm was positivist-quantitative, basic type, relational level, non-experimental design. The observational and inductive-deductive method was used. The probabilistic-stratified sample was 384 tourism employees from said region. The results showed that there is a direct and significant correlation between positive mental health and optimism in the context studied, with a bilateral significance level of less than 1%, as well as a Kendall's Tau b correlation strength of 0.445. It is concluded that the greater the mental well-being, the greater the work optimism.